Comprehensive analysis of the Spartina alterniflora WD40 gene family reveals the regulatory role of SaTTG1 in plant development - Yang, Maogeng; Chen, Shoukun; Geng, Jiahui; Gao, Shuqiang; Chen, Shihua; Li, Huihui (Frontiers in Plant Science, 2024)
The WD40 gene family, prevalent in eukaryotes, assumes diverse roles in cellular processes. Spartina alterniflora, a halophyte with exceptional salt tolerance, flood tolerance, reproduction, and diffusion ability, offers great potential for industrial applications and crop breeding analysis. The exploration of growth and developmentrelated genes in this species offers immense potential for enhancing crop yield and environmental adaptability, particularly in industrialized plantations. However, the understanding of their role in regulating plant growth and development remains limited.In this comprehensive study, we identified a total of 582 WD40 proteins in the S. alterniflora genome, exhibiting an uneven distribution across chromosomes. Through phylogenetic analysis, we categorized the 582 SaWD40 proteins into 12 distinct clades.Examining the duplication patterns of SaWD40 genes, we observed a predominant role of segmental duplication in their expansion. A substantial proportion of SaWD40 gene duplication pairs underwent purifying selection through evolution. To explore the functional aspects, we selected SaTTG1, a homolog of Arabidopsis TTG1, for overexpression in Arabidopsis. Subcellular localization analysis revealed that the SaTTG1 protein localized in the nucleus and plasma membrane, exhibiting transcriptional activation in yeast cells. The overexpression of SaTTG1 in Arabidopsis resulted in early flowering and increased seed size. These outcomes significantly contribute to our understanding of WD40 gene functions in halophyte species. The findings not only serve as a valuable foundation for further investigations into WD40 genes in halophyte but also offer insights into the molecular mechanisms governing plant development, offering potential avenues in molecular breeding.